A Historical Analysis of the Caste System: Origins and Evolution - Kafle, Dol Raj (HISAN: Journal of History Association of Nepal, 2024)
This study provides a comprehensive historical analysis of the caste system, focusing on its origins, evolution, and global impact. Originating from ancient Indian society, the caste system initially arose from the division of labour, categorizing people into groups based on occupation and birth. Over time, the system became more complex, influenced by social, economic, and political factors, and spread across South Asia, impacting neighboring regions like Nepal. Although much research has been conducted on the caste system, significant gaps remain, particularly regarding its early development, the socio-political dynamics shaping its structure, and its comparative role in other ancient civilizations such as Greece, Rome, Egypt, etc. This study aims to fill these gaps by exploring not only the Indian context but also drawing parallels with other societies. By employing a qualitative research approach and utilizing secondary sources, this study examines how caste was shaped by occupation, inter-caste relationships, and regional variations, with particular attention to the colonial and post-colonial perspectives. The research further situates the caste system within global frameworks of social hierarchy, highlighting its enduring influence on contemporary societies. This historical exploration seeks to enhance understanding of caste, emphasizing its significance as both a social identity and a mechanism for asserting rights within hierarchical structures.